Changing the carriers of cultural memory through the prism of Debray’s mediological theory - Vučković, Branislava (Sociološki pregled, 2022)
One of the basic theoretical attitudes of Debray’s mediological theory is deep interdependence of form and content of transmission (communication through time), i.e. carriers of the message and the message itself. Starting from that attitude and the hypothesis that change in the carriers of certain elements of cultural memory also leads to the change in its content, we have applied Debray’s analytical model of transmission elements in the analysis of different carriers of cultural memory in Kosovo and Metohija. The aim of the research is to determine necessary changes in the content of transmission process already caused as a consequence of the changed form of transmission, i.e. to detect, by applying the comparative method, whether part of the cultural heritage is lost in that manner or whether new media are suitable carriers of transmission.